Transparency, public reason and accountability in companies (2018)
This article revolves around the relationship between ethical accountability and transparency within the framework of business ethics. It is argued that, for the purpose of an audit to be really ethical rather than merely a tool to increase the levels of the reputation of the company, transparency must be inherent to accountability. To do this, it is claimed that the concept of transparency is analyzed should be seen from the point of view of civic ethics, in order to establish how it is implied in a normative approach to stakeholders theory. The article ends arguing that any process of accountability must include some minimal normative components of transparency for it to be applied in companies wanting to be considered as fair companies. © 2018 Pontificio Seminario Mayor San Rafael. All Rights Reserved.